KETERAMPILAN MANAJERIAL KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MADRASAH ALIYAHAL-FALAH ARUNGKEKE KABUPATENJENEPONTO - SULAIMAN Sulaiman (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstract. This study was designed using a qualitative descriptive approach correlational manifold. Collecting data using three types of questionnaires about managerial skills, leadership models, and teacher performance. Data were analyzed using descriptive statistics. The results showed that (1) A description and the principal forms of managerial skills very well belong to the category, as well as the performance of teacher MA Al-Falah Arungkeke Jeneponto classified as either category. This means that managerial skills with ability to approach the conceptual, technical, human relations affect the performance of teacher MA Al-Falah Arungkeke Jeneponto, (2) there is a significant positive implications in terms of principal leadership managerial skills to the improvement of teacher performance MA Al-Falah Arungkeke Jeneponto, this is explained by a score of 70 -85 % range, which means simultaneous principal leadership in terms of managerial skills in improving teacher performance MA Al-Falah Arungkeke Jeneponto entry in the category of good value. Based on these results, it is suggested to the principal in general, and a principal in the district in particular to pay attention and improve managerial skills and leadership models and with regard to other factors that affect the performance of teachers. Suggested for teachers to further optimize performance in accordance with the duties and responsibilities.